Healthcare-seeking behavior and awareness regarding snakebites and its first-aid management among tribal women in rural Maharashtra - Anuradha Kunal Shah; Ashwini Baburao Sapkal; Swati Deshpande (Wolters Kluwer Medknow Publications, 2023)
Background: In rural India, snake bite is a major health problem with high morbidity and mortality. Women have poor knowledge regarding snakebite and first aid measures and often resort to home remedies or visit traditional healers. This study was taken up to assess the healthcare-seeking behavior and awareness regarding snakebites and first-aid management among tribal women. Materials and Methods: This cross-sectional study was conducted from February to July 2019 in a tribal village, Palghar, Maharashtra. The sample size was 278. Women above the age of 18 years were selected by simple random sampling. A prevalidated semi-structured questionnaire was used for data collection which was done through door-to-door visit. Results: The mean age of the women was 36.59 years. Around 55.4% of women had good knowledge regarding snakebite and 39.9% of women had good knowledge of first aid in the event of Snakebite. Awareness regarding signs and symptoms in event of snakebite was good. The majority of the women preferred government medical facilities (71.58%) for the treatment of snakebite followed by traditional healers (20.14%). The main reasons for visiting traditional healers were transport difficulties, easy accessibility, and traditional beliefs and rituals. The most common form of first aid that was provided to the victims was tying of tight cloth/wire (72.86%), herbal medicines (30.85%), and use of "mantras" (8.17%). Conclusion: There is good knowledge regarding snakebites among tribal women, however, knowledge about appropriate first aid seems to be lacking. They are aware of the signs and symptoms and know how to prevent them however, preventive action is lacking. A targeted health education program focusing on these issues is the need of the hour.